2009
DOI: 10.1074/jbc.m806866200
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Variants of Duplex DNA Correlated with Cytosine-rich Chromosomal Fragile Sites

Abstract: We found that several major chromosomal fragile sites in human lymphomas, including the bcl-2 major breakpoint region, bcl-1 major translocation cluster, and c-Myc exon 1-intron 1 boundary, contain distinctive sequences of consecutive cytosines exhibiting a high degree of reactivity with the structure-specific chemical probe bisulfite. To assess the inherent structural variability of duplex DNA in these regions and to determine the range of structures reactive to bisulfite, we have performed bisulfite probing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
61
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 33 publications
6
61
0
Order By: Relevance
“…But the methylase probing studies indicate that the fragile zones are not single stranded for a large fraction of the time. Transient non-B conformations (called B/A-intermediate DNA) at the CCND1-MTC region and BCL2-MBR have been documented elsewhere, though these are still within the range of duplex conformations (4,9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But the methylase probing studies indicate that the fragile zones are not single stranded for a large fraction of the time. Transient non-B conformations (called B/A-intermediate DNA) at the CCND1-MTC region and BCL2-MBR have been documented elsewhere, though these are still within the range of duplex conformations (4,9).…”
Section: Discussionmentioning
confidence: 99%
“…1A and 2A). These zones are 100-to 1,000-fold more sensitive to breakage than the adjacent DNA regions located, for example, only 20 bp to either side of the fragile zone (2)(3)(4)(5)(6)(7). Hence, the DNA sequences surrounding each oncogene are not equally sensitive to breakage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Top1 reduction is likely to retard relaxation of negative supercoil. Excessive negative supercoil of DNA facilitates local structural alterations including R-loop, stem-loop, cruciform, triplex, and other non-B DNA structures in DNA rich in palindromes or G/C stretches like the S region, which probably inhibits the religation step of Top1 after cleavage (3,(8)(9)(10) (Figs. S7 and S8).…”
Section: Discussionmentioning
confidence: 99%
“…Lieber and colleagues reported that the bisulfite treatment of nuclear DNA from switch-induced spleen cells converted dC to dU in the S region, indicating the presence of single stranded DNA in the S region in activated B cells (6,7). R-loop may not survive long but lead to the formation of non-B structures including stem-loop, cruciform, and triplex in the S region because of abundant inverted repeats (3,(8)(9)(10).…”
mentioning
confidence: 99%